Redesigning the Madrasah Teacher Professional Education Curriculum through Ecotheological Literacy Integration to Address the Global Environmental Crisis - Rhamadanus Saefulloh (JURNAL ILMIAH GEMA PERENCANA, 2026)
The current environmental crisis is fundamentally a moral and spiritual challenge, yet the response from Islamic educational institutions, particularly madrasahs, remains constrained by a significant gap in ecotheological literacy among educators. This policy naskah addresses the critical lack of environmental spirituality integration within the Teacher Professional Education program and other in-service training structures, which are presently dominated by the rigid administrative and technical-pedagogical standards of the New Public Management paradigm. Such a bureaucratic focus has marginalized the transformative religious values essential for planetary survival, leading to a systemic "ecological blindness" within the educational environment. The methodology employed in this policy analysis follows a qualitative-descriptive and prescriptive approach, utilizing a synthetic review of curriculum frameworks and document analysis of existing teacher development programs. By evaluating current training modules through the lenses of critical ecopedagogy and transformative professionalism, this work formulates strategic interventions for curriculum redesign. The analysis proposes a radical shift from "how to teach" to "what to teach for planetary survival," emphasizing the integration of ecospiritual literacy as a core competency. It advocates for the revitalization of teacher working groups as collaborative laboratories for curriculum integration and the adoption of school-wide environmental approaches. Ultimately, this policy recommendation aims to transform madrasah teachers into catalysts for ecological change, ensuring that the institution fulfills its mandate as a guardian of the earth.